Norisoprenoid, phenolic and steroidal constituents from Mallotus luchenensis - Toan Phan, Nguyen Huu; Minh, Chau Van; Dang, Nguyen Hai; Thu Thuy, Dinh Thi; Phuong Thao, Nguyen Thi; Kiem, Phan Van; Thu, Vu Kim; Yvan Vander, Heyden; Joerlle, Quetin-Leclercq (Vietnam Journal of Chemistry, 2014)
A C13-norisoprenoid malloluchenoside (1), two phenolics gallic acid (2) and corillagin (3), and two steroids daucosterol (4) and stigmast-5-enee-3-O-(6-O-octadecanoyl-b-D-glucopyranoside) (5) were isolated from the MeOH extract of Mallotus luchenensis. Their structures were elucidated on the basis of spectral and physicochemical data. Among which, 1 was isolated for the first time from the nature. Key words: Mallotus luchenensis, norisoprenoid, phenolic, steroid, malloluchenoside.